Engineering neodymium-sensitized nanoconstructs for near-infrared enabled photomedicine - Yu, Zhongzheng (Nanyang Technological University, 2020)
Lanthanide-doped nanoconstructs have gained increasing attention in recent decades due to their unique properties, especially optical properties. The design of various lanthanide-based nanosystems are expected to contribute to medical and health applications, due to their advantageous properties such as excellent photostability, non-photobleaching and low cytotoxicity, etc. Among all kinds of lanthanide ions, neodymium (Nd3+) ions are highly favorable since they can absorb near-infrared light, specifically at 808 nm, and upconvert them to higher-energy light or heat. This biological transparent absorption can overcome the heating up effect caused by conventional ytterbium (Yb3+) ions sensitization. However, the low conversion efficiency and potential long-term toxicity of Nd3+-sensitized nanoconstructs are huge obstacles to their clinical translations. This thesis has contributed to this field in the design and fabrication novel Nd3+-sensitized nanoconstructs for near-infrared (NIR) enabled photomedicine, making them potentially safer, more efficient and closer to clinical usage.